PROSES BALIK NAMA SERTIPIKAT DALAM JUAL BELI TANAH MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (STUDI KASUS PUTUSAN PENGADILAN NEGERI BULUKUMBA NOMOR 26/Pdt.G/2019/PN Blk) - David Oberlin Nugraha Saragih; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2022)
Owning land, whether it's for residence or for business is a basic need. The validity as a land owner is proven by a certificate of ownership in the name of the owner. Land ownership can come from inheritance or purchase transactions. Purchase transactions should be carried out before a Notary/Land Deed Official in order to obtain a Sale and Purchase Deed. On the basis of the deed, the buyer can transfer the name of the land to the local Land Office in accordance with Government Regulation Number 24 of 1997 Article 37 which requires land registration. In purchase transactions, people often only go through private transactions so that the Sale and Purchase Deed is not obtained. This becomes a problem if the location of the seller or his heirs are not known so that the buyer cannot change the name of the certificate of ownership. To overcome this problem, there is a way that can be made, to file a lawsuit at the local District Court by attaching strong evidence and two witnesses. In the Bulukumba District Court Decision Number 26/Pdt.G/2019/PN Blk., the Panel of Judges granted the lawsuit with legal considerations, by examining all valid evidence, two witnesses who really knew the purchase transaction, conducting a local examination, and based on the laws and regulations. Based on the Court's Decision which grants the claim, the plaintiff can transfer the name of the certificate of ownership. This research uses normative and descriptive research.